Development of Non-Litigation Civil Dispute Settlement Model Based on Madurese Local Wisdom to Reduce Cases Accumulation in Court - Hasanah, Uswatun; Hamzah, Mohammad Amir; Winarwati, Indien (Faculty of Law, Universitas Brawijaya, 2019)
Madurese community prefer to settle civil disputes outside the court by generating peace between the parties in the form of undertable bond, while the mediation results outside the court, the legality is weak. In this regard, this study would like to produce model of non-litigation civil dispute settlement that guarantees binding force of settlement so have binding strength as well as dispute settlement through mediators in court. This research is normative-qualitative research, so the method is combination of legal research methods and sociological research methods. The study results indicate that the mechanism to settle civil disputes in Madura is carried out peacefully through consensus meetings with the mediators help. The mediation has the binding power of customary law because it is based on the voluntary willingness of the parties, carried out through deliberation. This is in line with the local wisdom values such as the value of maintaining